Risk Factors for Postoperative Events in Patients on Antiplatelet Therapy Undergoing Off-Pump Coronary Artery Bypass Grafting Surgery. (September 2020) - Cheng, Yujing; Liu, Xiaoli; Zhao, Yingxin; Sun, Yan; Zhang, Dai; Liu, Fang; Ma, Yue; Zhou, Yujie
This retrospective study assessed the risk factors for adverse events following off-pump coronary artery bypass graft (CABG) surgery with dual antiplatelet therapy (DAPT). Records (between 2013 and 2017) were reviewed for patients who discontinued DAPT (clopidogrel 75 mg and aspirin 100 mg) ≤5 days before off-pump CABG. The primary outcome was the incidence of a Bleeding Academic Research Consortium (BARC) type 4 major event. Factors associated with bleeding events and perioperative myocardial ischemia were evaluated using multivariable logistic regression. The incidence of major bleeding events was 17.6% in 2012 patients. Adjusted multiple logistic regression analysis showed that the risk of postoperative bleeding increased when DAPT was discontinued <3 days before surgery (day 2: adjusted odds ratio [OR]: 1.70, 95% confidence interval [CI]: 1.09-2.64; day 1: adjusted OR: 2.37, 95% CI: 1.49-3.77; day 0: adjusted OR: 2.45, 95% CI: 1.53-3.92). The adjusted risk of mortality (OR: 13.14, 95% CI: 4.55-37.94) was increased with bleeding complications. In subgroup analysis, perioperative myocardial ischemia was related to increased blood loss (adjusted OR: 1.10, 95% CI: 1.02-1.18). Aspirin and clopidogrel should optimally be discontinued> 3 days before CABG to reduce the risk of bleeding complications, myocardial ischemia, and death.